Zen and the art of motorcycle maintenance : an inquiry into values - Pirsig, Robert M. (Mariner Classics, 2024)
A narration of a summer motorcycle trip undertaken by a father and his son, the book becomes a personal and philosophical odyssey into fundamental questions of how to live.